1996
DOI: 10.1080/00206819709465358
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Galatean Volcanic Province, Turkey

Abstract: The Galatean volcanic province (GVP), located in northwestern Anatolia, is an ENE-WSW-oriented belt. The province as a whole corresponds to a depression filled with volcanic and sedimentary rocks. The northern margin of the GVP is truncated by the North Anatolian fault, whereas it is surrounded by a continental sedimentary pile interfingering with volcanics on the south. Field and aerial photographic studies reveal that the GVP consists of several volcanic complexes scattered throughout the province. Nine of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…Although the Galatean Arc Complex has been studied by many workers (Stchepinsky and Lahn 1941;Erol 1951Erol , 1954Erol , 1955Akyol 1969;Fourquin et al 1970;Ö ngür 1977;Ach 1982;Akyürek et al 1984;Kazanci and Gökten Copyright # 2003 John Wiley & Sons, Ltd. 1988; Tankut et al 1990;Türkecan et al 1991;Koçyi git 1991a, b;Keller et al 1992;Gökten et al 1996;Toprak et al 1996;Wilson et al 1997), not all the volcanic rocks and associated sedimentary intercalations in the volcanic plateau have yet been fully distinguished and mapped on a 1:25 000 scale. This paper therefore aims to draw attention to one of those hitherto unidentified exposures of accessible volcanic rocks, exposed on the southern side of the Galatean volcanic plateau, the Saraçköy Volcanic Suite.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although the Galatean Arc Complex has been studied by many workers (Stchepinsky and Lahn 1941;Erol 1951Erol , 1954Erol , 1955Akyol 1969;Fourquin et al 1970;Ö ngür 1977;Ach 1982;Akyürek et al 1984;Kazanci and Gökten Copyright # 2003 John Wiley & Sons, Ltd. 1988; Tankut et al 1990;Türkecan et al 1991;Koçyi git 1991a, b;Keller et al 1992;Gökten et al 1996;Toprak et al 1996;Wilson et al 1997), not all the volcanic rocks and associated sedimentary intercalations in the volcanic plateau have yet been fully distinguished and mapped on a 1:25 000 scale. This paper therefore aims to draw attention to one of those hitherto unidentified exposures of accessible volcanic rocks, exposed on the southern side of the Galatean volcanic plateau, the Saraçköy Volcanic Suite.…”
Section: Introductionmentioning
confidence: 98%
“…Until recently, only Lower-Middle Miocene volcanic rocks and coeval continental sedimentary sequences were included in the so-called 'Galatean Volcanic Province', which was used for the stratigraphic column of Miocene volcanic rocks by Toprak et al (1996). At the same time Gökten et al (1996) suggested that, based on field studies in the south-southwestern part of the area, volcanic activity started in the Late Oligocene and evolved until the Early Pliocene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the folds within the Upper Miocene units (near site 128) are perpendicular to crl. Tankut et al (1995) and Toprak et al (1996)]; 3, tncik Formation; 4, ~andlr Formation; 5, Tu~lu Formation; 6, S~eymanh Formation; 7, Bozklr Formation; 8, Deyim Formation; 9, alluvium; 10, syncline; 11, anticline; 12, overturned syncline; 13, thrust faults; 14, reverse faults; 15, normal faults; 16, strike-slip faults or faults with an unknown sense of movement; 17, photo-lineaments; 18, dextral strike-slip faults; 19, sinistral strike-slip faults; 20, dips of faults where they are best observed in the field; 21, sample site locations. Plots of fault planes: (b)-(e) fault planes, slickenlines and stress orientations for each site; (f)-(i) whole data in a particular phase and subarea (lower hemisphere equal area projections).…”
Section: Palaeostress Inversionmentioning
confidence: 99%
“…1A), which belongs to the Pontide Tectonic Belt (Toprak et al 1996, Wilson et al 1997, Tankut et al 1998). The GVP evolved as a consequence of the collision of the Afro-Arabian and Eurasian plates (Rögl 1998).…”
Section: Age and Geologic Settingmentioning
confidence: 99%